Immunoglobulins, Immunoglobulin G Subclasses and Complement C3,C4 Levels in Adult Epileptic Patients on Carbamazepine and Sodium Valproate (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objective:To assess the effects of long-term antiepileptic monotherapy (carbamazepine or sodium valproate ) on the levels of some immunological parameters ( immunoglobulins IgA, IgG, IgM , immunoglobulins G subclasses IgG1, IgG2, IgG3, IgG4 and complements C3, C4 in adult epileptic patients. Subjects and Methods: Eighty –one adult epileptic patients were included in this study , 43 on carbamazepine monotherapy and 38 on sodium valproate monotherapy , with 50 apparently healthy subjects age and sex matched taken as a control group . From both patients and control group 10 ml venous blood sample were taken and immunoglobulin serum levels (IgA, IgG, IgM) , immunoglobulin G subclass (G1, G2, G3, G4) and complement C3,C4 were assessed using kits ( Fitzgerald Industries Int. USA). Results: There was a significant reduction in IgM and IgG2 in epileptic patients on carbamazepine and a significant reduction in IgM, IgG2 and IgG4 in epileptic patients on valproate in comparison with controls. Conclusion: Carbamazepine and sodium valproate as long-term antiepileptic monotherapy have some effects on the immune-system parameters in adult epileptics.